Supplementary polio immunization activities and prior use of routine immunization services in non-polio-endemic sub-Saharan Africa - Stephane Helleringer; Jemima A Frimpong; Jalaa Abdelwahab; Patrick Asuming; Hamadassalia Touré; John Koku Awoonor-Williams; Thomas Abachie; Flavia Guidetti (The World Health Organization, 2012)
OBJECTIVE: To determine participation in polio supplementary immunization activities (SIAs) in sub-Saharan Africa among users and non-users of routine immunization services and among users who were compliant or non-compliant with the routine oral poliovirus vaccine (OPV) immunization schedule. METHODS: Data were obtained from household-based surveys in non-polio-endemic sub-Saharan African countries. Routine immunization service users were children (aged < 5 years) who had ever had a health card containing their vaccination history; non-users were children who had never had a health card. Users were considered compliant with the OPV routine immunization schedule if, by the SIA date, their health card reflected receipt of required OPV doses. Logistic regression measured associations between SIA participation and use of both routine immunization services and compliance with routine OPV among users. FINDINGS: Data from 21 SIAs conducted between 1999 and 2010 in 15 different countries met inclusion criteria. Overall SIA participation ranged from 70.2% to 96.1%. It was consistently lower among infants than among children aged 1-4 years. In adjusted analyses, participation among routine immunization services users was > 85% in 12 SIAs but non-user participation was > 85% in only 5 SIAs. In 18 SIAs, participation was greater among users (P < 0.01 in 16, 0.05 in 1 and < 0.10 in 1) than non-users. In 14 SIAs, adjusted analyses revealed lower participation among non-compliant users than among compliant users (P < 0.01 in 10, < 0.05 in 2 and < 0.10 in 2). CONCLUSION: Large percentages of children participated in SIAs. Prior use of routine immunization services and compliance with the routine OPV schedule showed a strong positive association with SIA participation.